2018
DOI: 10.1002/dmrr.3071
|View full text |Cite
|
Sign up to set email alerts
|

The dual effect of C‐peptide on cellular activation and atherosclerosis: Protective or not?

Abstract: C-peptide is a cleavage product of proinsulin that acts on different type of cells, such as blood and endothelial cells. C-peptide biological effects may be different in type 1 and type 2 diabetes. Besides, there are further evidence for a functional interaction between C-peptide and insulin. In this way, C-peptide has ambiguous effects, acting as an antithrombotic or thrombotic molecule, depending on the physiological environment and disease conditions. Moreover, C-peptide regulates interaction of leucocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 97 publications
0
14
0
4
Order By: Relevance
“…Another reasonable explanation is that C-peptide indirectly contributes to depression through its role in promoting atherosclerosis. A previous study has demonstrated that the deposit C-peptide on intima layer of the vessels promotes infiltration of monocytes/macrophages and lymphocytes CD4+, with impacts on the atherogenesis process [ 33 35 ]. Cerebrovascular atherosclerosis causes arterial stenosis, which leading to hemodynamic disturbance as well as low perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Another reasonable explanation is that C-peptide indirectly contributes to depression through its role in promoting atherosclerosis. A previous study has demonstrated that the deposit C-peptide on intima layer of the vessels promotes infiltration of monocytes/macrophages and lymphocytes CD4+, with impacts on the atherogenesis process [ 33 35 ]. Cerebrovascular atherosclerosis causes arterial stenosis, which leading to hemodynamic disturbance as well as low perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Structural bridges between A and B chains of proinsulin molecule [20] Stimulates Na + -K + -ATPase expression/activity [25] Modulates eNOS and iNOS activities and thereby hemodynamic states [20,26] Induces intracellular signaling especially Ca 2+ -dependent pathways [20,26] Modulates gene transcription/expression [20] Modulates glucose metabolism [20] Effects on cell survival [10] Modulates thrombotic events [27,28] Modulates lipid metabolism [29-31] Table 1; known physiological functions of c-peptide (eNOS=endothelial nitric oxide synthase, iNOS=inducible nitric oxide synthase)…”
Section: Physiologic Functions Of C-peptidementioning
confidence: 99%
“…Previous studies have shown the association between Cpeptide and cardiovascular disease (19). Michelle et al examined the effect of C-peptide on atherosclerosis and found that high C-peptide levels were related with increased lipid deposits and smooth muscle cell proliferation in the vessel wall, contributing to atherosclerosis (12). Antonio Cabrera de Leon et al found that elevated C-peptide was associated with the incidence of myocardial infarction and coronary artery disease in the general population (20).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that C-peptide has been widely used as a biomarker of diabetes diagnosis in clinical practice. Observational studies have found the association between Cpeptide and cardiovascular diseases (12,13). High levels of Cpeptide could increase the risks of atherosclerosis and myocardial infarction (14,15).…”
mentioning
confidence: 99%